The Influence of Job Satisfaction on Turnover Intention with Organizational Commitment as a Mediator for Employees of PT. ABC Factory Unit - Rohmani Dayyan, Inayah; Miranda, Fadila; Amalia Lubis, Rizka (Lafadz Jaya Publisher, 2024)
This study aims to see the effect of job satisfaction on turnover intention with organizational commitment as a mediator in the employees of PT ABC Factory Unit. This study uses statistical calculations of linear regression analysis, carried out on employees of PT ABC Factory Unit, totaling 60 employees. Based on the results of the normality test output, the Shapiro-Wilk significance results were obtained for turnover intention, job satisfaction, and organizational commitment of 0.165; 0.328; and 0.682 (p> 0.05), so that all data obtained can be said to be normally distributed. Then overall employee turnover intention is in the high category with a mean of 44.52; overall employee job satisfaction is in the medium category with a mean of 85.38; and overall employee organizational commitment is in the medium category with a mean of 46.67.Based on the research significance level of sig. 0.046 (p <0.05) with this it can be said that H1 which states that there is an effect of job satisfaction on turnover intention is acceptable; research significance level of sig. 0.039 (p <0.05) with this it can be said that H2 which states that there is an effect of organizational commitment on turnover intention can be accepted; research significance level of sig. 0.019 (p <0.05) with this it can be said that H3 which states that there is an effect of organizational commitment on job satisfaction is acceptable; and based on the results of data analysis, the results show that organizational commitment mediates the effect of job satisfaction on turnover intention, so that it can be said that H4 is accepted.